2016
DOI: 10.1590/1807-7692bar2016160004
|View full text |Cite
|
Sign up to set email alerts
|

Management Practices as Capabilities Leading to Superior Performance

Abstract: This paper has three main contributions to the debate about the value of management practices. First, the empirical confirmation of a strong and significant relationship between the level of management practices and three major dimensions of firms' performance (profitability, growth and productivity). The value of this contribution is grounded on a survey of 124 companies in a focused and careful choice of context: packaging industry in an emerging country, Brazil. Second, our theoretical conceptualization of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 75 publications
3
14
0
4
Order By: Relevance
“…The results of the hypotheses obtained from the PLS analysis suggests that managerial practices, employees' skills and expertise and supplier involvement have significantly and positively influenced R&D firms' performance. This finding is consistent with that of previous studies in a non-R&D setting (Brito and Saisan, 2016;Larteb et al, 2015;Carr and Pearson, 2002). Brito and Saisan (2016) revealed that proficient lean managerial practices in terms of planning, organizing, implementation and control have optimized resource utilization and enhanced firms' performance.…”
Section: Reliability Testsupporting
confidence: 92%
“…The results of the hypotheses obtained from the PLS analysis suggests that managerial practices, employees' skills and expertise and supplier involvement have significantly and positively influenced R&D firms' performance. This finding is consistent with that of previous studies in a non-R&D setting (Brito and Saisan, 2016;Larteb et al, 2015;Carr and Pearson, 2002). Brito and Saisan (2016) revealed that proficient lean managerial practices in terms of planning, organizing, implementation and control have optimized resource utilization and enhanced firms' performance.…”
Section: Reliability Testsupporting
confidence: 92%
“…Instead, iterative and learning capabilities related to an effectuation perception of the entrepreneurial event can provide firms with competitive edges that do not require traditional planning and control practices (Sarasvathy, 2001). In any case, innovation-driven entrepreneurial firms in Brazil often lack managerial and organizational capabilities (Cahen et al , 2016; Brito and Sauan, 2016), thus revealing an overall need for KIE firms to further develop such skills.…”
Section: Discussionmentioning
confidence: 99%
“…The studies conducted with Brazilian companies support the heterogeneity of management practices, but limitations in their sample sizes (Padrão, Motta, & Vieira, 2009) and in their focus on single industries (Brito & Sauan, 2016;Mauro & Brito, 2011) jeopardize more detailed assessment of this phenomenon. Therefore, we include the following hypothesis for the relationship between sectoral competition and the level of companies' management practices: BAR, Rio de Janeiro, RJ, Brazil, v. 15, n. 4, art.…”
Section: Industries' Characteristics and Management Practicesmentioning
confidence: 97%
“…BAR, Rio de Janeiro, RJ, Brazil, v. 15, n. 4, art. 4, e180028, 2018 www.anpad.org.br/bar Data collection followed the procedures adopted by Bloom and Van Reenen as well as by studies that have already replicated those authors' research in Brazil (Brito & Sauan, 2016;Mauro & Brito, 2011;Padrão et al, 2009). Based on those studies, we evaluated seven topics: Management Operations, Human Resources and Incentives, Goals, Performance Control, Sustainability, Technological Innovation and Innovation in Management.…”
Section: Sampling and Data Collectionmentioning
confidence: 99%